Reducing Primigravida Anxiety: A Comparison of Audiovisual Spiritual Emotional Freedom Technique Therapy and Educational Video - Nasution, Nadhiati Awlia; Rachmawati, Anita; Nurihsan, Juntika (Jambura Medical and Health Science Journal, 2026)
Introduction: Primigravida pregnant women are vulnerable to anxiety, worry, and fear during pregnancy, childbirth, and postpartum period. If not managed properly, anxiety during pregnancy can negatively affect maternal and fetal outcomes, including pre-eclampsia, premature birth, miscarriage, impaired uteroplacental blood flow, low birth weight, congenital abnormalities, as well as postpartum stress and depression. Complementary therapies such as the Spiritual Emotional Freedom Technique (SEFT), have been suggested as non-pharmacological strategies to alleviate anxiety. This study aimed to compare the effectiveness of audiovisual-based SEFT therapy and antenatal class educational videos in reducing anxiety levels among primigravida pregnant women.Methods: This study used a quasi-experimental nonequivalent control group design conducted in two groups with 27 respondents in each group. Respondents were asked to fill out the Pregnancy Related Anxiety Questionnaire-Revised 2 (PRAQ-R2) before the first day of treatment and after the third day of treatment to determine anxiety scores, then compared and statistically analyzed using Wilcoxon and Mann-Whitney test.Results: Anxiety scores significantly decreased in the audiovisual-based SEFT group (p 0.001) and were significantly greater than in the antenatal educational video group (p = 0.046).Conclusion: Audiovisual media-based SEFT therapy is more effective in reducing anxiety in primigravida pregnant women than educational videos for pregnant women.Keywords: Anxiety, primigravida, spiritual emotional freedom technique